Internalization of Recombinant Tissue-Type Plasminogen Activator by Isolated Rat Hepatocytes is via Coated Pits - Marks, Gary J; Hart, Timothy K; Rush, Glenn F; Hoffstein, Sylvia T; Fong, Kei-Lai L; Bugelski, Peter J (Thrombosis and Haemostasis, 1990)
The uptake and internalization of tissue-type plasminogen activator (t-PA) by freshly isolated rat hepatocytes was investigated. Electron microscopic examination of the uptake of t-PA-colloidal gold conjugates (t-PA-gold) by isolated rat hepatocytes showed that t-PA-gold was internalized via coated pits. This was inhibited with excess t-PA. Uptake of 125I-t-PA by isolated rat hepatocytes was a rapid, saturable, and specific process. The initial rate of specific uptake was 0.1 fmol/106 cells per min. The specific uptake plateaued at 1.4 fmol/106 cells by 30 min and declined to 0.8 fmol/106 cells at 2 h. Depletion of cellular ATP by 85-90% did not affect the initial rate of specific uptake. However, specific uptake by ATP-depleted hepatocytes at 30 min was reduced by 37%. By 2 h specific uptake by ATP-depleted hepatocytes was only 5% lower than by untreated hepatocytes, suggesting that processing of t-PA and/or its receptor is ATP-dependent. Uptake of 125I-t-PA was temperature dependent. Specific uptake was reduced by ∼20% at 22° C and by 70% at temperatures below 16° C. Finally, inhibition of coated pit formation by K+-depletion with nigericin decreased the uptake of 125I-t-PA. This inhibition was shown to be K+-specific since treatment with nigericin in the presence of K+ did not inhibit coated pit formation or 125I-t-PA uptake. A threshold K+-depletion level for inhibition of coated pit formation was also demonstrated since treatment under conditions that reduced cellular K+ by only 54% had no effect on coated pit formation or 125I-t-PA uptake. These data support our hypothesis that internalization of t-PA by isolated rat hepatocytes is via coated pits and suggest that uptake of t-PA is a receptor-mediated process.